The Problem of Analgesia in Thoracic Surgery and Ways of Its Solution - V. Kh. Timerbayev; P. G. Genov; V. Yu. Lesnik (Общая реаниматология)
Pain syndrome after thoracic surgery is a serious problem that is far from being solved today. In the early postoperative period, the patients who have undergone thoracotomy or thoracoscopy have very severe pain that is more intense than that after operations on the abdomen, limbs, and brain. The development of postoperative chronic pain remains an urgent problem as before when the patients of thoracic surgical units continue to experience chest pain and insensitivity months and even years after surgery. In addition to the ethical aspect of the problem associated with a patient’s right to adequate analgesia, there is a risk for pulmonary dysfunction in patients for whom the analgesia mode has been inadequately chosen, which favors the development of pulmonary and cardiac complications. As of now, the proposed analgesia procedures include thoracic epidural analgesia, multi-segmental paravertebral and intercostal block, subpleural block, the use of infiltration anesthesia in combination with general anesthesia, surgical wound irrigation with local anesthetics, and some other methods. In this review, the authors have attempted to summarize today’s gained knowledge of anesthesia for thoracic surgery and to denote some new and promising areas in the treatment of pain. Key words: thoracic surgery, pain, analgesia, postoperative analgesia, hyperanalgesia.